Pengaruh Konsentrasi dan Interval Waktu Pemberian Pupuk Organik Cair (POC) Nasa terhadap Pertumbuhan dan Produksi Tanaman Bawang Merah ( Allium Ascolonicum L) - Pandu Winata; Armaini Armaini; Zulfatri Zulfatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
This study aims to determine the effect of the concentration of nasa, the interval of giving organic liquid organic fertilizer and get the best treatment on the growth and production of shallot plants.The research has been conducted at Experimental Garden of Agriculture Faculty of Riau University from February to April 2020 using a randomized block design whit two factors and three replications.The first factor is the concentration of (POC) Nasa which consist of three levelsconcentration 3 ml.l-1, 4 ml.l-1 and 5 ml.l-1. The second factor is the time interval which consists of three levels, every 3 days, 5 days, and 7 days.The parameters observed were plant  height, harvest age, number of tubers per clump, tuber diameter, weight of fresh tubers per plot, and weight of tubers that werw fit for storage per plot. Data analysis used variance and continued whith Duncan’s multiple-range test at the 5%. The results showed that the treatment of several concentration of POC Nasa  had a significant effect on tuber diameter and tuber weight per plot. Spraying time interval treatment significantly affected tuber diameter, fresh tuber weight per plot, and weight tuber worth saving per plot. The interaction of POC Nasa and spraying time interval did not have a significant effect on all parameters plant  height, harvest age, number of tubers per clump, tuber diameter, weight of fresh tubers per plot, and weight of tubers that werw fit for storage.Keywords :shallot, concentration POC Nasa, spraying interval.